Anàlisi contrastiva: antecedents i perspectives - Cuenca, Maria Josep; Ramos, Joan Rafael (Caplletra. Revista Internacional de Filologia, 2001)
This presentation article reviews the main landmarks in the history of Contrastive Analysis as a perspective in the study of language that can be included in both Theoretical and Applied Linguistics. After this general introduction to the subject of the volume, the papers are presented.